Queer Necropolitics in the Decapolis: Here and There, Now and Then - McLellan, Peter N. (Biblical interpretation, 2020)
This article seeks to disrupt the deadly deployment of boundaries that mark particular people as normative or queer, socially living or dead. Conversing with the Decapolis of Mark 5:1-20 and Washington D.C.’s prostitution free zones (pfz), the present project deploys a hauntological and critical spatial response, that locates points of contact between transwomen of color in the U.S. capital and the possessed Gerasenes. This article challenges biblical scholars to lean into historiography that sees such stories—from the tombs and from the pfz—as politically active in and of themselves, and with one another. Mark 5:1-20 is imagined here as a place constructed by alliances of queer bodies spatialized into unlivability. Such alliances are resources for thinking beyond the neocapitalist drive to create deadly normativity through insides and outsides, suggesting that biblical texts are always already infused with demands from places where life is suffocated.